2014
DOI: 10.18268/bsgm2014v66n2a12
|View full text |Cite
|
Sign up to set email alerts
|

Equinoideos del Cretácico Tardío del Norte de Coahuila, México

Abstract: ResumenEn el presente trabajo se describen diez especies de equinodermos fósiles que han sido colectados en varios afloramientos de la Formación Austin (Cretácico Superior) localizados en los arroyos El Freno y El Tecolote, dentro del municipio de Jiménez, norte de Coahuila. La presencia de los ammonites Scaphites hippocrepis y Delawarella delawarensis en las secciones estudiadas permite asignar a estas capas una edad de Campaniano inferior. Algunos taxa aquí reportados como Cidaris texanus Clark, Salenia mexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…In a previous work carried out by Vega et al (2013) at Austin Formation, in the vicinity of the study area, he reported the presence of the ostreids Phrysaea (Gryphaea) aucella and Exogyra laeviscula, the ammonoid Parapuzosia boisei and two species of the genus Menabites as well as the crustacean (Decapoda) species Enoploclytia tepeyacensis. According to Silva-Martínez et al (2014) the presence of the ammonite Delawarella delawarensis (Morton, 1841) along the studied section supports the assignment of a Lower Campanian age for this unit.…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…In a previous work carried out by Vega et al (2013) at Austin Formation, in the vicinity of the study area, he reported the presence of the ostreids Phrysaea (Gryphaea) aucella and Exogyra laeviscula, the ammonoid Parapuzosia boisei and two species of the genus Menabites as well as the crustacean (Decapoda) species Enoploclytia tepeyacensis. According to Silva-Martínez et al (2014) the presence of the ammonite Delawarella delawarensis (Morton, 1841) along the studied section supports the assignment of a Lower Campanian age for this unit.…”
Section: Introductionsupporting
confidence: 67%
“…The description of three echinoids specimens of the genus Diplodetus reported by Silva-Martínez et al (2014) Continental shelf environments, the presence of soft seafloor, and organic matter in the sediment, which represent a food source for endobenthonic organisms, are the main features that define a scenario that contribute to the developement of detritivore organism, such as D. brisenoi in the Austin Formation of northeastern Mexico.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations